Regulatory Aspects of Cleaning and Cleaning Validation in Active Pharmaceutical Ingredients - Debaje, Priyanka D; Chhabra, Gurmeet S.; Gujarathi, Nayan (Asian Journal of Pharmaceutical Research and Development, 2018)
Pharmaceutical product and active pharmaceutical ingredients (APIs) can be contaminated by other pharmaceutical products or APIs, by cleaning agents, by microorganisms or by other materials e.g. air borne particles, dust, lubricants, raw materials, intermediates, etc. In the manufacturing of the pharmaceutical products, it is a must to reproduce consistently the desired quality of product. Residual material from the previous batch of the same product or from different product may be carried to the next batch of the product, which in turn may alter the quality of the subjected product. An effective cleaning shall be in place to provide documented evidence that the cleaning method employed within a facility consistently controls potential carryover of product including intermediates and impurities, cleaning agents and extraneous material into subsequent product to a level which is below predetermined level The purpose of this review is to provide information about importance of cleaning validation of API in pharmaceutical industry and this information is in accordance with the regulatory guidelines